Does Circadian Variation of Mothers Affect Macronutrients of Breast Milk? - Çetinkaya, Aslihan Köse; Dizdar, Evrim Alyamaç; Yarcı, Erbu; Sari, Fatma Nur; Oguz, Serife Suna; Uras, Nurdan; Canpolat, Fuat Emre (American Journal of Perinatology, 2017)
Objective To determine the within-day variation of fat, protein, and carbohydrate content of breast milk.Methods The study was conducted at Zekai Tahir Burak Maternity Teaching Hospital between April 2013 and January 2014. We obtained milk samples from lactating mothers of hospitalized infants through hand expression after breast-feeding or pumping three times a day. A mid-infrared human milk analyzer was used for measuring the macronutrient contents of breast milk samples.Results Lactating mothers of 52 infants (30 preterm, 22 term) were recruited to the study. No significant difference was found in protein, fat, and carbohydrate content of milk samples throughout the day. We compared within-day variation of macronutrients of transitional and mature milk, milk samples from the mothers of preterm and term infants, and samples collected by either hand expression or pumping. We did not find a significant difference between the groups.Conclusion Absence of circadian variations in lipid, carbohydrate, and protein content of breast milk in our study may be related to ethnic differences, maternal nutritional status, different milk content measurement technique, and population characteristics.
Keywords: breast milk; circadian variation; macronutrient; infant; mid-infrared human milk analyzer